The horror at Camp Jellyjam - Stine, R. L. (New York : Scholastic, 1995)
The counselors at King Jellyjam's sports camp seem just a little too happy and a little too obsessed with winning, and their game of softball is not just a game
4-6
8-12
460
Accelerated Reader AR
Keywords: Camping -- Juvenile fiction; Horror fiction